Prevalence of Skin Reactions to Aeroallergens in Asthmatics of Puerto Rico - Montealegre, Federico; Quiñones, Carmen; Michelen, Victoria; Bayona, Manuel; Fernández-Caldas, Enrique; Vazques, Orlando; Colón, Félix; Chardón, Domingo; García, María (Puerto Rico Health Sciences Journal, 2019)
see manuscript